Needs Assessment of Innovative Leadership Development of Administrators Under the Secondary Education Service Area Office Nakhon Phanom - Phosri, Ackara (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) examine the current state and the desirable state of innovative leadership among school administrators, 2) assess the priority needs for developing innovative leadership of school administrators, and 3) propose guidelines for the development of innovative leadership among school administrators. The sample consisted of 339 school administrators and teachers under the Secondary Educational Service Area Office Nakhon Phanom, selected through multistage random sampling. The research instrument was a five-point Likert scale questionnaire. The questionnaire on the current state demonstrated content validity indices ranging from 0.60 to 1.00, discrimination indices between 0.27 and 0.75, and a reliability coefficient of 0.95. The questionnaire on the desirable state showed content validity indices ranging from 0.60 to 1.00, discrimination indices between 0.27 and 0.96, and a reliability coefficient of 0.95. Data were analyzed using frequency, percentage, mean, standard deviation, and the Priority Needs Index (PNI). The research findings revealed that: 1. The current state of innovative leadership among school administrators was at a high level overall, while the desirable state was at the highest level. 2. The overall priority needs for developing innovative leadership had a Priority Needs Index value of 0.297. The three highest priority areas were creativity, teamwork and participation, and transformational vision, respectively. 3. The guidelines for developing innovative leadership among school administrators comprised three dimensions: creativity, teamwork and participation, and transformational vision. A total of 28 development guidelines were identified, and overall, the proposed guidelines were rated at the highest level of appropriateness.